THE RELATIONSHIP OFTHE EFFECTIVENESS OF INTERPERSONALCOMMUNICATION, WORKING AGE AND JOB TENUREWITH ORGANIZATIONAL COMMITMENT - Vera Anitra; Tri Astuti (Universitas Muhammadiyah Kalimantan Timur, 2020)
The purpose of this study was to find the relationship between the effectiveness of interpersonal communication, working age and job tenure with organizational commitment. The method used in this study was a quantitative method using a questionnaire as a data collection tool. The data analysis used in this study is multiple regression analysis which was processed by a data analysis program called Statistical Package for the Social Sciences (SPSS). Participants in this study were employees at PT. Pupuk Kalimantan Timur with several predetermined criteria such as; regular employees and employees whose last education was high school or equivalent. The results of this study found that the effectiveness of interpersonal communication, working age and job tenure were able to predict employees’ organizational commitment. Other results were the effectiveness variables of interpersonal communication was the most influential variable on increasing organizational commitment and then followed by variables of working age and job tenure. The results of this study are expected to be one of the strategies that can be used by companies to increase organizational commitment.